Peramalan Titik Akuifer Di Desa Manistutu Kecamatan Melaya Kabupaten Jembrana Dengan Metode Geolistrik - Sukarasa, Ketut; Suardana, Putu (Kappa Journal, 2023)
Research has been carried out which aims to determine the depth of the aquifer point in Manistutu Village, Melaya District, Jembrana Regency. The work process of this research is the first to collect data directly using a geoelectric device with a Wenner configuration. Electric current is passed below the earth's surface through current electrodes that are installed above the earth's surface. The data that has been collected is then processed using Res2Div version 3.53g for 2D. The result of the software is a 2D image which is a direct lateral view of the subsurface structure. Of the two identified paths, namely line 1 at initial coordinates 8°31'92.33"S, 114°55'94.59"E to final coordinates 8°31'78.07"S, 114°56'05.21"E, the lowest resistivity value is obtained 121 Ohm m with a depth of 13 m and 20 – 32 m which is suspected as an aquifer point. On track 2 with initial coordinates 8°31'55.56"S, 114°56'08.31"E to final coordinates 8°31'55.56"S 114°56'61.11"E the resistivity value is 2.56 Ohm m to 8952 Ohm m. The layer that is suspected as an aquifer point is at a depth of 18.5 m, because of its low resistivity value.